2014
DOI: 10.1371/journal.pgen.1004262
|View full text |Cite
|
Sign up to set email alerts
|

FAK Acts as a Suppressor of RTK-MAP Kinase Signalling in Drosophila melanogaster Epithelia and Human Cancer Cells

Abstract: Receptor Tyrosine Kinases (RTKs) and Focal Adhesion Kinase (FAK) regulate multiple signalling pathways, including mitogen-activated protein (MAP) kinase pathway. FAK interacts with several RTKs but little is known about how FAK regulates their downstream signalling. Here we investigated how FAK regulates signalling resulting from the overexpression of the RTKs RET and EGFR. FAK suppressed RTKs signalling in Drosophila melanogaster epithelia by impairing MAPK pathway. This regulation was also observed in MDA-MB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…Consistent with this idea, Ret expression leads to both Src42A and Fak phosphorylation, but we find that the two kinases have opposing effects on proliferation: Src42A promotes proliferation downstream of Ret, whereas Fak blocks it. Hence, despite the fact that blocking Fak function may represent a therapeutic opportunity in some cancers (Ashton et al , 2010; Lee et al , 2015), our findings are more aligned with a previous study (Macagno et al , 2014) that suggested that, at least in the context of Ret‐driven tumorigenesis, Fak can act as a tumour suppressor. In future, it will also be of interest to explore how the Ras/Raf/Erk pathway, activated by Ret in other contexts and previously shown to affect ISC proliferation in flies (Buchon et al , 2010; Biteau & Jasper, 2011; Jiang et al , 2011), intersects with Src/Fak/Wg signalling in response to Ret activation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Consistent with this idea, Ret expression leads to both Src42A and Fak phosphorylation, but we find that the two kinases have opposing effects on proliferation: Src42A promotes proliferation downstream of Ret, whereas Fak blocks it. Hence, despite the fact that blocking Fak function may represent a therapeutic opportunity in some cancers (Ashton et al , 2010; Lee et al , 2015), our findings are more aligned with a previous study (Macagno et al , 2014) that suggested that, at least in the context of Ret‐driven tumorigenesis, Fak can act as a tumour suppressor. In future, it will also be of interest to explore how the Ras/Raf/Erk pathway, activated by Ret in other contexts and previously shown to affect ISC proliferation in flies (Buchon et al , 2010; Biteau & Jasper, 2011; Jiang et al , 2011), intersects with Src/Fak/Wg signalling in response to Ret activation.…”
Section: Discussionsupporting
confidence: 87%
“…Both Ret and Src kinases can phosphorylate Fak in vitro (Erpel & Courtneidge, 1995;Plaza-Menacho et al, 2011). In the context of gain-of-function Ret mutations, different studies have reached opposite conclusions regarding the ability of Fak to enhance or suppress Ret-driven neoplasia (Panta et al, 2004;Plaza-Menacho et al, 2011;Sandilands et al, 2012;Macagno et al, 2014). Concurrent with Wg induction and pSrc upregulation, Ret expression in adult intestinal progenitors led to a small but detectable induction of pFak ( Fig 4F).…”
Section: Ret-dependent Phosphorylation Of Src42a and Fak Kinases Affementioning
confidence: 99%
“…To determine the molecular changes at the GB front in relation with the activity of integrins, we immunostained GB brain samples with Talin, a mediator of integrin adhesivity (45), and with Focal Adhesion Kinase (FAK), a cytoplasmic Tyrosine kinase involved in signaling and cytoskeleton dynamics associated to integrin activity (46,47). We analyzed confocal mi- To confirm the functional contribution of integrins to GB progression and validate these suggestions, we used specific RNAi constructs to knockdown myospheroid (mys), the Drosophila Integrin B subunit, or rhea, the Drosophila Talin, two key players for integrin function.…”
Section: Resultsmentioning
confidence: 99%
“…John et al and Bianchi et al have shown that inhibition of GSK3β decreased phosphorylation of FAK during cell spreading and migration (44, 45). FAK has been known to regulate the recycling of receptor tyrosine kinases back to the plasma membrane (46). This is the first report regarding the role of FAK in the regulation of receptor internalization.…”
Section: Discussionmentioning
confidence: 99%